Use or rice husk ash an addition in mortar - Julián Salas; Percy Castillo; M. Isabel Sánchez de Rojas; Janer Veras (Materiales de Construccion, 1986)
With the aid of a 400-litre capacity pilot furnace, in which 40 Kg of rice husk is submitted to controlled combustion, an ash (RHA) is obtained for use as an addition, the physicochemical properties of which form the focal point of this work. Results will also be presented for the combustion power of the husk ≃ 4000 kcal/kg, being greater than half the value for normal bituminous coals. Conglomerates have been obtained by mixing RHA with different proportions of lime and portland cement, and their properties are studied with regard to both mortars and concretes. The ultimate aim of the work is to demonstrate how rice husk (world production of which is estimated at 500.106 m3 per annum) may be feasibly applied as an addition, without forgetting its excellent properties as a fuel, which makes it particularly suitable for developing countries with a shortage of cement and energy resources.